2015
DOI: 10.1089/lgbt.2014.0126
|View full text |Cite
|
Sign up to set email alerts
|

Female Couples Undergoing IVF with Partner Eggs (Co-IVF): Pathways to Parenthood

Abstract: Our analysis presents descriptive data and sheds realistic expectations for Co-IVF couples. Co-IVF cycles can result in a shared experience with regard to the process of creating a family, while preserving a female couple's desire for dual partner participation in the gestational process. We encourage centers treating female couples to consider departing from traditional nomenclature of "donors" and "recipients" and adopting the nomenclature "Co-IVF" to describe the modern understanding of the shared experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 10 publications
3
21
0
Order By: Relevance
“…The more difficult requests are those where couples opt for the procedure that is more risky and/or less likely to be successful. They may choose to use the eggs of the oldest partner or may decide to use the eggs of the partner with a known genetic risk 3. Obviously, the higher these ‘costs’ and extra disadvantages are, the more likely that the clinic will deny them the treatment.…”
Section: Proportionalitymentioning
confidence: 99%
See 1 more Smart Citation
“…The more difficult requests are those where couples opt for the procedure that is more risky and/or less likely to be successful. They may choose to use the eggs of the oldest partner or may decide to use the eggs of the partner with a known genetic risk 3. Obviously, the higher these ‘costs’ and extra disadvantages are, the more likely that the clinic will deny them the treatment.…”
Section: Proportionalitymentioning
confidence: 99%
“…They called it ‘reception of oocyte from partner’ or ROPA. The number of requests for this application seems to be growing 2 3. The application is interesting because it resembles several known practices such as egg donation and surrogacy and at the same time differs from these practices.…”
Section: Introductionmentioning
confidence: 99%
“…The receiving partner's average age was 40.0 AE 2.9, and the sharing partner's average age was 34.8 AE 3.5. Additionally, the study observed that 76% of the co-IVF couples achieved at least one pregnancy, as compared with 46% in the study of Marina et al 8,12 Given the small number of individuals in these studies and paucity of literature with conflicting results, more studies are needed to evaluate the influence of various factors on success rates of co-IVF.…”
Section: Same-sex Female Couples: Treatment Strategymentioning
confidence: 93%
“…To achieve this, women of SSFCs typically elect to undergo DIUI before pursuing ART including in vitro fertilization (IVF), both of which are conducted with an anonymous or known sperm donor. 8 Although the use of DIUI and/or IVF offers patients the ability to become pregnant, give birth, and secure a desired genetic link for one of the partners, DIUI can also provide, although limited, an opportunity for the nongenetic mother to actively participate by assisting the medical staff with the insemination. 4,5,9 Consequently, fertility evaluations and decisions about which treatment to undergo when only one woman desires to be the genetic mother and become pregnant are not influenced by sexual orientation.…”
Section: Same-sex Female Couples: Treatment Strategymentioning
confidence: 99%
See 1 more Smart Citation